Tooth contact analysis of a designed planetary gear drive for the vehicle industry (Journal of Production Engineering, 2023)
A planetary gear drive consists of a sun gear, planet pinions and an internal gear. We designed a complex gear system which is usable in the field of the vehicle industry into the automatized robots. The system was designed by GearTeq software which is connected with the SolidWorks designer software. After the assembly and the motion simulations tooth contact analysis (TCA) was made to analyse the normal stresses and the normal deformations on the connecting surface of the planet pinions and the internal gear by different load moments.
Keywords: Planetary gear drive; CAD; TCA; normal stress; normal deformation; analysis